Fashion exhibitions in art spaces: particularities of the brazilian and carioca context (Revista de Ensino em Artes, Moda e Design, 2021)
The purpose of this article is to discuss fashion exhibitions in art spaces in the city of Riode Janeiro as a cultural phenomenon, inserted in the unique context of cultural policies inBrazil between 1980 and 2010. In the international scenario, this period corresponds to aneffervescence of these events in renowned museums and galleries, arousing the attentionof the press and specialized critics around the controversial relationship between luxurycompanies and artistic institutions. The study of the cases in Brazil delimits the need toconsider brazilian economic and political reality that crosses the field of culture. Thus,pointing to particular reconfigurations in the dialogues between art and fashion.
Keywords: Fashion; Art; Institution